RGS3L allows for an M2 muscarinic receptor-mediated RhoA-dependent inotropy in cardiomyocytes - Lévay, Magdolna; Krobert, Kurt A.; Vogt, Andreas; Ahmad, Atif; Jungmann, Andreas; Neuber, Christiane; Pasch, Sebastian; Hansen, Arne; Müller, Oliver J.; Lutz, Susanne; Wieland, Thomas (Basic research in cardiology, 2022)
The role and outcome of the muscarinic M2 acetylcholine receptor (M2R) signaling in healthy and diseased cardiomyocytes is still a matter of debate. Here, we report that the long isoform of the regulator of G protein signaling 3 (RGS3L) functions as a switch in the muscarinic signaling, most likely of the M2R, in primary cardiomyocytes. High levels of RGS3L, as found in heart failure, redirect the Gi-mediated Rac1 activation into a Gi-mediated RhoA/ROCK activation. Functionally, this switch resulted in a reduced production of reactive oxygen species (− 50%) in cardiomyocytes and an inotropic response (+ 18%) in transduced engineered heart tissues. Importantly, we could show that an adeno-associated virus 9-mediated overexpression of RGS3L in rats in vivo, increased the contractility of ventricular strips by maximally about twofold. Mechanistically, we demonstrate that this switch is mediated by a complex formation of RGS3L with the GTPase-activating protein p190RhoGAP, which balances the activity of RhoA and Rac1 by altering its substrate preference in cardiomyocytes. Enhancement of this complex formation could open new possibilities in the regulation of the contractility of the diseased heart.
Im Titel ist "2" bei M2 tiefgestellt
Gesehen am 09.06.2022